Peningkatan Kapasitas UMKM dalam Pembukuan Sederhana dan Pemanfaatan QRIS untuk Pembayaran Digital di Era Modern - Tandi Rizki Apridianto (Penerbit Jurnal Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening the structure of Indonesia's national economy, especially through their contribution to opening up job opportunities and improving the welfare of the wider community. In the midst of the rapid growth of MSMEs, adaptation to digital technology is a necessity to support business efficiency. One of the relevant innovations is the implementation of QRIS (Quick Response Code Indonesian Standard), a digital payment standard regulated by Bank Indonesia to improve convenience, security, and financial inclusion. Through a community service approach, training and introduction related to simple bookkeeping and digital payments were carried out for MSME actors in Tahu Gejrot cart which aims to find out more about finance and current digital technology in order to make it easier for business actors to conduct business and transactions through QRIS by making financial reports according to Financial Accounting Standards (SAK) and utilizing digital payments with QRIS. Practicing the process of making simple financial statements to creating a QRIS Account. As a result, sales actors get a new perspective and provide a new breakthrough for their businesses towards financial report information and digital payments through QRIS so as to motivate business actors to develop in financial problems and face the development of digitalization that will make it easier for buyers and sellers to transact through current technology.